2015
DOI: 10.1134/s1087659615030177
|View full text |Cite
|
Sign up to set email alerts
|

Shielding efficiency of lead borate and nickel borate glasses for gamma rays and neutrons

Abstract: Gamma ray exposure buildup factor (EBF) and neutron shielding efficiency of borate glass sys tems in composition (100 -x -y) Na 2 B 4 O 7 -xPbO-yNiO (where x and y = 0, 2, 4, 6, 8 and 10 weight per centage) were investigated in the present study. Gamma ray EBF values were computed using Geometric Pro gression (G P) method for photon energy 0.015 to 15 MeV up to penetration depths of 40 mfp (mean free path). The macroscopic effective removal cross sections for fast neutron (2 to 12 MeV) were calcu lated. At low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…To overcome these demerits of lead, researchers are in ease to fabricate a lead free shielding material, which is light weight and effective in absorbing high energy radiations. Research efforts is enhancing day by day, such that, a few studies have been reported on polymer composite radiation shields over the globe, whereas in India, studies are being carried out mainly on glass based radiation shields, and a very few on polymers composites . The chief advantage of using polymers as a matrix is the low cost, easy processability, good chemical resistance, low specific gravity and light weight.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these demerits of lead, researchers are in ease to fabricate a lead free shielding material, which is light weight and effective in absorbing high energy radiations. Research efforts is enhancing day by day, such that, a few studies have been reported on polymer composite radiation shields over the globe, whereas in India, studies are being carried out mainly on glass based radiation shields, and a very few on polymers composites . The chief advantage of using polymers as a matrix is the low cost, easy processability, good chemical resistance, low specific gravity and light weight.…”
Section: Introductionmentioning
confidence: 99%
“…While health concerns discourage the use of toxic lead, the usage of concrete has space constraints. Different glass systems incorporating heavy metals have been investigated for radiation shielding [1][2][3][4][5] as they have the advantage of less toxicity and being transparent to visible light. Significant research efforts towards designing lightweight, flexible, and cost-effective radiation shields have focused on polymer composites for radiation shielding applications [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the search for materials that can attenuate hazardous radiation, lead and lead oxide glasses have proven to offer effective shielding to X-rays and γ-rays, 1-4 due to the high density, high atomic number, and high resistance to chemical corrosion of lead. 16,17 Now the focus has shifted to lightweight, cost-effective, and optically transparent polymer composites, which can take any shape, as radiation shields. 5,6 High-density materials like concrete, which have effective shielding properties and are inexpensive and easy to fabricate, become weaker at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] The presence of oxides of low-Z elements like beryllium, lithium, and boron in glasses helps to slow down fast neutrons and capture slower neutrons. 16,17 Now the focus has shifted to lightweight, cost-effective, and optically transparent polymer composites, which can take any shape, as radiation shields. Polymers like polyamide 6, low-density polyethylene, polypropylene, polystyrene, poly(methyl methacrylate), kapton polyimide, and isophthalic resin filled with suitable high-Z elements have drawn attention for their gamma-attenuation properties.…”
Section: Introductionmentioning
confidence: 99%